Co-processing of common plastics with pistachio hulls via hydrothermal liquefaction. (1st February 2020) - Hongthong, Sukanya; Raikova, Sofia; Leese, Hannah S.; Chuck, Christopher J.
Highlights: HTL was used to co-process 4 common plastics with pistachio hulls. Over 35% bio-crude yields were obtained. PET is mainly broken down into aqueous phase products. Nylon-6 breaks down almost entirely to the source monomer. PE and PP remain largely intact through out the process. Abstract: Mixed, wet, plastic streams containing food waste residues are being increasingly collected at point of use, but are extremely challenging to recycle and are therefore largely sent to landfill. While a challenging waste problem, this also represents an underutilised feedstock, which could be co-processed with biomass, increasing the scope of products, easing out seasonal variation in biomass production and increasing the production capacity of a traditional biorefinery. One promising method of biomass conversion is hydrothermal liquefaction (HTL), where lignocellulosic residues are broken down in water at high temperatures and pressures to produce a bio-crude oil, a solid residue and an aqueous fertiliser. In this study, the co-processing of common plastic waste with pistachio hulls was assessed to investigate the suitability of the HTL approach. The HTL of pistachio hulls was undertaken at 350 °C over 15 and 60 min, with four commonly used plastics: polyethylene, polypropylene, PET and nylon-6, in blends of up to 20 wt% plastic to biomass. A novel FT-IR method was developed to estimate the conversion of plastics in the system, and the product phases were fully analysed. High yields of up to 35% bio-crude were achieved, and under optimal conditions, nylon-6 and PET were found to break down almost completely in the system. PET generated numerous products that distributed predominantly into the aqueous phase; the major decomposition product of nylon-6 was found to be the monomer ∊-caprolactam, also largely partitioning into the aqueous phase. The polyolefins were less reactive; a limited degree of decomposition formed oxidised products, which distributed into the bio-crude phase. This result represents a highly promising method for waste plastic valorisation.